Pertumbuhan, Produksi dan Kandungan Gizi Beberapa Varietas Sorgum Lokal (Sorghum bicolor .L) Pada Lahan Kering - Yovita Yasintha Bolly; Fiator Nong (Agriculture - Jurnal Ilmu Pertanian, 2022)
The research was carried out in Renggarasi Village and Runut Village (Lodang and Holak) which took place from December 2021 to July 2022. The aim of this research was to examine the growth and production of local sorghum varieties in Lodong and Holak (Runut Village) and in Renggarasi (Tanawawo Village) and to find out the nutritional content of several local sorghum varieties. The research took place in several stages, namely land preparation, planting, replanting, maintenance, observation, harvesting, and analysis of sorghum and soil samples in the laboratory. The research results showed that the highest vegetative growth of sorghum plants came from the Lodong area, (Runut) and the lowest from Renggarasi Village (Tanawawo). Meanwhile, the highest dry shelled seed weight came from Renggarasi, a type of red sorghum and the lowest came from Holak, a type of red sorghum. And the highest water content comes from Tanawawo, namely the black sorghum type, the lowest from Holak, the white round type. The carbohydrate content is in accordance with the National sorghum nutritional content standards, while protein and fat are still below the standards.